LOYALITAS PELANGGAN DITINJAU DARI DIGITAL MARKETING, BRAND TRUST, DAN KUALITAS PRODUK PADA HOUSE OF DONATELLO CABANG SOLO - Dinar Ayu Novendasari; Bambang Mursito (JURNAL ILMIAH EDUNOMIKA, 2020)
The purpose of this study is to determine whether there is a significant influence between digital marketing variables, brand trust, and product quality on customer loyalty. In addition, it is also to find out whether there is a significant simultaneous effect and which variable is the most dominant in influencing customer loyalty at the House of Donatello, Solo Branch. The method used is quantitative descriptive method. The research period is March to June 2020. The population in this study is all people who shop at the House of Donatello, Solo Branch and the sample used is 100 respondents, where the sampling technique uses random sampling techniques. The data used are primary data and secondary data with questionnaire data collection techniques. Data analysis techniques in this study used multiple linear tests with SPSS version 21. The results of the study can be concluded that: 1) The influence of digital marketing, brand trust, and product quality on customer loyalty at the House of Donatello Solo Branch, 2) The influence of digital marketing on customer loyalty at the House of Donatello Solo Branch, 3) The influence brand trust on customer loyalty at the House of Donatello Solo Branch, 4) The influence of product quality on customer loyalty at the House of Donatello Solo Branch. Keywords: Customer Loyalty, Digital Marketing, Brand Trust, and Product Quality